Stress-strain response on the 3D angle interlock woven fabric polymer composite / Muhammad Nasrun Faris Mohd Zulkifli - Mohd Zulkifli, Muhammad Nasrun Faris (2018)
Textile woven materials are widely used as woven composite to replace steel due to the strength-weight ratio factor on certain reinforcement application such as aerospace, transportation, defence, and sports. 3D woven fabric have enticed many researchers around the world to explore the potential mechanical tensile strength performance area particularly on 3D angle interlock (3DAI) woven fabric. The aim of this research are to analyse the relationship between stress-strain properties of 3DAI with different weft densities and draw-in plan and to establish the correlation between 3DAI woven fabric and composite stress with different weft densities and draw-in plan. 3DAI woven fabric samples were manufactured by using a Sulzer rapier loom based on different fabric setup parameters such as draw-in plan (DRW); DRW 1 - 4 and variation number of weft densities; 14,18,22,25 pick.cm-1. Later, a BJC-39 epoxy resin and hardener were used to fabricate the 3 DAI woven composite through a hand lay-up approach.